The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11356-017-8823-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of pore structure of several biochars with 3D imaging

Abstract: Pore space characteristics of biochars may vary depending on the used raw material and processing technology. Pore structure has significant effects on the water retention properties of biochar amended soils. In this work, several biochars were characterized with three-dimensional imaging and image analysis. X-ray computed microtomography was used to image biochars at resolution of 1.14 µm and the obtained images were analysed for porosity, pore-size distribution, specific surface area and structural anisotrop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 30 publications
(36 reference statements)
4
41
1
Order By: Relevance
“…Thereafter, images were segmented into voids and solids by global thresholding. The threshold value was determined with an automatic approach described by Hyväluoma et al (2018b), which is based on the methods of Otsu (1979) and Hapca et al (2013). Finally, the binary image was processed with a majority filter (radius 2), and isolated solid objects larger than 1000 voxels were removed from the images.…”
Section: X-ray Microtomography and Image Analysismentioning
confidence: 99%
“…Thereafter, images were segmented into voids and solids by global thresholding. The threshold value was determined with an automatic approach described by Hyväluoma et al (2018b), which is based on the methods of Otsu (1979) and Hapca et al (2013). Finally, the binary image was processed with a majority filter (radius 2), and isolated solid objects larger than 1000 voxels were removed from the images.…”
Section: X-ray Microtomography and Image Analysismentioning
confidence: 99%
“…Obtained grey-scale images were filtered and segmented as described in a previous paper [19]. As in that paper, a fully automatic segmentation algorithm based on a modified version of Otsu's method [22] was used to avoid operator-dependent bias in the results.…”
Section: X-ray Microtomography and Image Analysismentioning
confidence: 99%
“…D A values close to unity describe isotropic pore structure and higher values indicate stronger structural anisotropy. In [19], D A was determined for several biochars derived from different feedstock and biochars with an anisotropic pore structure resulting from vascular cell structure had D A > 20.…”
Section: X-ray Microtomography and Image Analysismentioning
confidence: 99%
“…It was found that biochar sample (B3), stored under the relative humidity of 56-74%, absorbed water in the amount of 5% by mass. Biochars are porous materials and their pore structure has the effects on the water absorption and water retention properties [58]. Gray et al [59] stated that water uptake by biochars is dependent on both feedstock, which controls residual macroporosity and production temperature, which controls hydrophobicity and pyrogenic nanopore formation.…”
Section: Hygroscopicity Of Brown Coal Biochar and The Selected Brownmentioning
confidence: 99%